OUTCOME OF THE CHOICE OF WOUND CLOSURE TECHNIQUE IN EMERGENCY LAPAROTOMY - Rafiq, Muhammad Kashif; Haider Kamran,; Sultan, Babar; Khan, Yousuf Aziz; Wadud, Fazli; Ayub, Muhammad; Ali, Saad; Ali, Ammad (Journal of Ayub Medical College Abbottabad, 2022)
Background: Abdominal surgeries are the most common surgeries performed around the world. Closure of abdominal wound is important and a number wound closing techniques are in practice. This study was conducted to determine the outcome of the choice of wound closure technique in emergency laparotomy. Methods: It was a retrospective study from March-September 2019, conducted at the Surgical A unit, Ayub Teaching Hospital, Abbottabad. Ninety-five patients aged 22-60 years, who underwent emergency laparotomies via midline and para-median incisions were included in the study. Results: There were 74 (77.89%) males and 21 (22.11%) females. Anatomical closure technique was used in 67 (70.53%) of study participants while mass closure technique was used in 28 (29.47%) of study participants. 50 (52.63%) patients had anaemia, 27 (28.42%) had hypo-proteinemia, and 14 (14.74%) developed peritonitis. Post-operative wound infection was noticed in 15 (15.79%) patients. Out of 95 patients, 19 (20%) developed burst abdomen. Overall, 5 (5.26%) patients died in the hospital. All cases of burst abdomen occurred within first two weeks of hospital stay (p= 0.004), had an association with peritonitis (p=0.0001) and post-operative wound infection (p= 0.005). Wound closure technique was not associated with development of post-operative complications including burst abdomen (p >0.05). Conclusion: Post-operative complications occur independently of wound-closure technique and surgeons should have a low threshold for prevention of post-operative complications where possible.